Influence of marital status on the treatment and survival of middle-aged and elderly patients with primary bone cancer - Wen, Yixin; Zhang, Hui; Zhi, Kaining; Li, Minghui (Frontiers in Medicine, 2022)
Objective The role of spousal support has been recognised to benefit patients with many chronic diseases and cancers. However, the impact of marital status on the survival of middle-aged and elderly patients with primary bone tumours remains elusive. Methods The data of patients aged ≥ 45 years with primary bone tumours diagnosed between 2000 and 2018 were extracted from the Surveillance, Epidemiology, and End Results Database. Kaplan–Meier analysis was used to assess the overall survival and tumour-specific survival of patients. The Cox proportional hazards and Fine-and-Gray models were used to calculate the hazard ratios (HRs) and sub-distribution HRs (sHR) and the corresponding 95% confidence interval (CI) of all-cause mortality and tumour-specific mortality, respectively. Results A total of 5640 primary bone tumours were included in the study. In 45-59 years, cohort, married, unmarried, divorced and widowed accounted for 66.0%, 21.0%, 11.2% and 1.8%, respectively; while 64.3%, 10.1%, 8.8% and 16.8% in 60+ years cohort, respectively. The widowed patients had a lower proportion of early-stage tumours at diagnosis than that of married, unmarried, and divorced patients (31.0% vs. 36% vs. 37.1% vs. 39.4%; P =0.008), and had a higher proportion of patients who did not undergo surgery than that of married, unmarried, and divorced patients (38.6% vs. 21.3% vs. 24.6% vs. 24.4%; P <0.001). The widowed population had an increased risk of all-cause mortality (HR, 1.68; 95% CI, 1.50–1.88; P <0.001) and disease-related mortality (HR, 1.33; 95% CI, 1.09–1.61; P =0.005) compared with the married population. Conclusions the marital status of middle-aged and elderly people can affect the tumour stage at diagnosis, treatment, and survival prognosis of patients with primary bone cancer. Widowed patients are more inclined to choose non-surgical treatment and have the worst prognosis.